Antimicrobial properties of anacardium occidentale (Cashew) leaf extract against staphylococcus aureus and escherichia coli - Mohd Ali Jinah, Nor Ain Nabihah; Ahmad Yusof @ Hanafi, Hanani; Mat Jusoh, Hanapi (IIUM Press, 2020)
Introduction: Anacardium occidentale (cashew) leaf has been recognized as a potential source of natural antibacterial and antimicrobial compounds. Aims: This study investigated the antimicrobial properties of Anacardium occidentale (cashew) leaves extract against the most common human pathogenic bacteria specifically Staphylococcus aureus and Escherichia coli. Materials and methods: Anacardium occidentale leaves were extracted using 70% methanol. The antimicrobial activities of the extracts were evaluated by determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) value. Results: The results showed that both bacteria were sensitive towards the leaves extract. However, E. coli was more sensitive towards the leaves extract than S. aureus which showed the lowest inhibitory concentration at 0.353 mg/ml and 0.705 mg/ml respectively. In addition, there was no significant different between the minimal concentrations of leaves extract that can kill both bacteria. The result also showed that no colony present in agar plates for both bacteria at concentration 2.821 mg/ml. Conclusion: Therefore, it can be concluded that Anacardium occidentale (cashew) leaves extract are effective as antimicrobial agent against S. aureus and E. coli bacteria.